(untitled) (Global Journal of Medical Research, 2020)
Introduction The objective of this study is to compare the outcomes of Modified Desarda repair no mesh and Lichtenstein repair for inguinal hernia Patients and Methods This is a prospective randomized controlled trial study of 1242 patients having 1313 hernias operated from January 2008 to December 2018 640 patients were operated using Lichtenstein repair and 602 using Desarda repair The variables like age sex location type of hernia tolerance to local anesthesia duration of surgery pain on the first third and fifth day hospital stay complications re-explorations morbidity and time to return to normal activities were analyzed Follow up period was from 1-10 years median 6 5 years Results There were no significant differences regarding age sex location type of hernia and pain in both the groups The operation time was 52 minutes in Modified Desarda group and 42 minutes in the Lichtenstein group that is significant p 0 05